Partner distress in the context of adult anorexia nervosa: The role of patients' perceived negative consequences of AN and partner behaviors. Issue 1 (4th August 2014) - Fischer, Melanie S.; Baucom, Donald H.; Kirby, Jennifer S.; Bulik, Cynthia M.
ABSTRACT Objective Romantic partners can play an important role in the recovery from anorexia nervosa (AN). It is important to understand partners' behaviors and variables associated with their own distress. The aim was to examine associations of patients' perceived negative consequences of AN, behavioral strategies employed by partners, and partner distress. Method We used a cross‐sectional design to assess associations between self‐reports of patients' perceived negative consequences of AN, partners' caregiver distress, negative affect, relationship satisfaction, and observational coding measures of partners' behavioral strategies of change promotion and acceptance/validation. Sixteen adult patient‐partner dyads in committed relationships were assessed at baseline of a couple‐based intervention for AN. Results Partners' change promotion moderated the association between patients' perceived negative consequences of AN and partners' caregiver distress. Partners' acceptance/validation was associated with partners' negative affect. Discussion This report represents the first description of specific partner behaviors in the context of AN. Partners who reported the least distress were those who were trying to promote changes in AN behaviors in patients who reported high negative consequences of AN, and partners who were trying to show understanding of the patients' experience. Future studies should examine the impact of partner behaviors on AN treatment outcome. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:67–71)